Long-term effects of lowland sawah system on soil physicochemical properties and rice yield in Ashanti Region of Ghana - Obalum, S. E.; Oppong, J.; Nwite, J. C.; Watanabe, Y.; Buri, M. M.; Igwe, C. A.; Wakatsuki, T. (Spanish Journal of Agricultural Research, 2012)
Lowland sawah is viewed as a sustainable alternative to traditional rice culture in West Africa. Sawah (a bund-demarcated, puddled, leveled, and water-regulated rice field) has received growing research attention lately, but no data exist yet on the system’s long-term agronomic impact. In a clayey inland-valley soil in southern Ghana, 10-year-old sawah plots (OSP), fresh sawah plots (FSP), and non-sawah plots (NSP) were maintained under both ponded and non-ponded conditions in 2007. The OSP enhanced soil status of exchangeable nutrients compared to NSP. There were relative improvements in soil bulk density, total porosity, and field moisture content (OSP ≥ FSP > NSP), with clear benefits of ponding over non-ponding in OSP. The NSP was so unsustainable that it showed less favourable values of these variables than an adjacent fallowed plot. These soil variables deteriorated with time, with significant differences in FSP. Soil moisture retention data for tension range of 0-300 kPa depicted the importance of puddling and ponding. During 2001-2009, OSP consistently out-yielded NSP by five times on average. During 2007-2009 when all three plots co-existed, grain yields averaged 5.80, 4.80 and 1.10 Mg ha−1 in OSP, FSP and NSP, respectively. In 2007 yields, OSP minus FSP was higher than NSP; in 2008/2009, the opposite prevailed. These results highlight the agronomic benefits of continuous sawah-based rice production. Although the positive effects of puddling on the soil hydrophysical properties were largely responsible for the wide margin in yield between sawah and traditional systems, the latter lacked other yield-enhancing factors, particularly bunds for water control, were also lacking in the latter.